Pengaruh LDR, ROE, DER, NIM, NPL, CAR Terhadap Harga Saham Sektor Perbankan Konvensional Periode 2014-2018 - Dwi Riska Nabila; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of loan to deposit ratio, return on equity ratio, debt to equity ratio, net interest margin, non-performing loans and capital adequacy ratios on share prices in conventional banking sub-sectors registered in the Indonesia Stock Exchange in the 2014-2018 period. Samples were taken using a purposive sampling method, so that of 44 banks listed on the IDX, 37 banks were found that met the criteria. Data were analyzed using multiple linear regression methods with panel data through EViews 9. The results of this study indicate that non-performing loans have an influence on stock prices. While the loan to deposit ratio, return on equity ratio, debt to equity ratio, net interest margin, and capital adequacy ratio have no effect on stock prices